2022
DOI: 10.1007/s11187-022-00623-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional entrepreneurial ecosystems: learning from forest ecosystems

Abstract: Despite the emerging body of literature on entrepreneurial ecosystems (EEs), theoretical development is still in its infancy. In this article, we explicitly draw upon the analogy of forest ecosystems (FEs) with an EE to extrapolate the regional entrepreneurial ecosystem (REE) as an alternate conceptual framework. The REE considers a region’s socioeconomic activity and the stability of its performance as a whole, influenced by partitioned interests of economics, social arrangements, physical environment, knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 100 publications
0
4
0
2
Order By: Relevance
“…O'Connor and Audretsch (2022) explicitly use the analogy of a forest ecosystem, when conceptualizing an EE and present an alternative theoretical framework to generalize the regional entrepreneurial ecosystem. The authors consider the regional entrepreneurial ecosystem as the socioeconomic activity of a region and the permanency of its performance, influenced by factors such as shared economic interests, social activities, physical environment, knowledge, and technology, all of which contribute to the industry and economic order of the community.…”
Section: Exploring Ee Within Existing Technological and Social Challe...mentioning
confidence: 99%
“…O'Connor and Audretsch (2022) explicitly use the analogy of a forest ecosystem, when conceptualizing an EE and present an alternative theoretical framework to generalize the regional entrepreneurial ecosystem. The authors consider the regional entrepreneurial ecosystem as the socioeconomic activity of a region and the permanency of its performance, influenced by factors such as shared economic interests, social activities, physical environment, knowledge, and technology, all of which contribute to the industry and economic order of the community.…”
Section: Exploring Ee Within Existing Technological and Social Challe...mentioning
confidence: 99%
“…Hay que recalcar en el trabajo de Moore (1993) la comparación del ciclo de vida de los ecosistemas biológicos, el cual incluye el nacimiento, expansión, liderazgo y autorrenovación/muerte, con características observadas en las empresas o agrupaciones empresariales, lo que fue un factor decisivo para que se popularizara el uso de una alegoría biológica para construir el término "ecosistemas de emprendimiento". Es importante anotar que la emergencia de este concepto implica el cambio de foco del estudio del emprendimiento, pasando del individuo y de la firma hacia las regiones, definidas tanto por las comunidades como por el espacio geográfico que ocupan (O'Connor & Audrestch, 2022).…”
Section: Theodoraki Dana Y Caputo 2022unclassified
“…En esta misma línea, estos autores ya sopesaban en un trabajo previo(Mason & Brown, 2014) ciertas limitaciones al identificar características genéricas de los ecosistemas, debido a que estos surgen bajo condiciones y circunstancias particulares.Adicionalmente, Stan (2015) y Spigel y Harrison (2017) estiman que se presenta una serie de factores y características que no ofrece ningún tipo de razonamiento sobre sus causas y efectos o cómo se adhieren entre sí.Un asunto conceptual que es ignorado frecuentemente y en el cualMason y Brown (2014, 2017 son reiterativos tiene que ver con la dimensión temporal de los ecosistemas.Al no profundizar en este aspecto, es muy difícil establecer en qué momento un ecosistema se afianza definitivamente o por qué otros fallan bajo circunstancias parecidas. En esta parte, es importante señalar que algunos autores identifican que ninguno de los aspectos reconocidos en los ecosistemas indican su existencia, pero, en virtud de los arreglos y las interacciones de los elementos, se terminan convirtiendo en atributos de un ecosistema de emprendimiento(O'Connor & Audrestch, 2022).…”
unclassified
“…By questioning these distinctions between EEs and clusters we have shown that the EE concept has considerable conceptual ambiguity within its internal definitions but also in its demarcations with other concepts, reifying its position as a chaotic concept. Given the similarities and conceptual lineage of these concepts, a conceptual endeavour needs to occur that explores the dynamic interactions of clusters and EEs as distinct but interrelated systems (Autio et al, 2018; Martin and Sunley, 2015), particularly if EEs are to be considered to exist primarily at the regional scale and be integral to the region’s stability and changing socio-economic structure (O’Connor and Audretsch, 2022). This means seeing them in relation to each other, not as isolated phenomena (see, for example, Auerswald and Dani, 2017), and with a more precise understanding of the distinctions between the concepts.…”
Section: The Conceptual Ambiguity Between Entrepreneurial Ecosystems ...mentioning
confidence: 99%